Working Position, Work Duration, Ergonomics Knowledge Level on The Risk of Musculoskeletal Disorders among Informal Workers in Slipper Sponge Sandal Manufacturing - Prasasti, Sari Arum; Suwoyo, Suwoyo; Retnaningtyas, Ekowati (Jurnal Ilmiah Kesehatan, 2026)
The informal sector may be associated with an increased risk of occupational diseases or accidents. This is due to the absence of an ergonomic workplace, insufficient attention to occupational safety and health, and inadequate supervision. The purpose of this study was to determine the effect of working position, work duration, and level of ergonomic knowledge on the risk of Musculoskeletal Disorders (MSDs) among informal workers in slipper sponge sandal manufacturing. The research design in this study was cross- sectional. The number of respondents was 33. Data collection used field observation and the completion of questionnaires using the REBA (Rapid Entire Body Assessment), Nordic Body Map Questionnaires, and questionnaires measuring ergonomic knowledge. Data analysis used bivariate and multivariate analysis. Multivariate analysis used multiple linear regression with α=0.05. Results showed that 63.6% respondents had a high risk of MSDs. Based on bivariate analysis, working position (X1) obtained p=0.018, work duration (X2) p=0.018, ergonomic knowledge level (X3) p=0.023. Multivariate analysis on X1, X2, and X3 got p=0.000. In conclusion, Working position, work duration, and ergonomic knowledge level influence partially and simultaneously the risk of musculoskeletal disorders among informal workers in slipper sponge sandal manufacturing.